An excerpt from “Macbeth” by W. Shakespeare, translated and interpreted by Anna Akhmatova - L. G. Kihney; A. V. Lamzina (Научный диалог, 2020)
The translation of an excerpt from Shakespeare’s tragedy “Macbeth”, made by A.A. Akhmatova in 1933 is considered in the article. The results of a comparative analysis of the original text and the translation text are presented. The question of the purpose of translation is raised: it is proved that Akhmatova did not intend to translate the text of the tragedy in full, and the translation of the passage she performed was not a sketch for a failed translation, but an attempt to plunge into the semiosphere of “Macbeth”. The relevance of the study is due to a detailed analysis of the translation text, which had not previously been subjected to thorough literary research. The novelty of the research is seen in the fact that in the translation performed by Akhmatova the authors highlight semiotic shifts concerning the image of Macbeth: it differs in Akhmatova’s interpretation from Shakespeare’s. The authors dwell on the textual gaps of translation and show their importance for understanding the image of Macbeth: Akhmatova eliminates in the text all the moments that could characterize Macbeth positively. Particular attention is paid to references to Macbeth that appeared in Akhmatova’s work after her translation of the above passage. It has been proven that this translation became the generator of Akhmatova’s own artistic ideas, developed in the “Shakespearean” key.